2020
DOI: 10.21203/rs.3.rs-31775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico virtual screening-based study of nutraceuticals predicts the therapeutic potentials of folic acid and its derivatives against COVID-19

Abstract: The recent outbreak of the novel coronavirus (SARS-CoV-2) in the Wuhan province of China has taken millions of lives worldwide. In this pandemic situation and absence of known drugs and vaccines against novel coronavirus disease (COVID-19), there is an urgent need for the repurposing of the existing drugs against it. So, here we have examined a safe and cheap alternative against this virus by screening hundreds of nutraceuticals compounds against known therapeutic targets of SARS-COV-2 by molecular docking .Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Phensuximide was found in molecular docking simulations of FDA-approved small compounds associated with protection against COVID-19, M pro [ 35 ]. In VS-based study, magnesium ascorbate, a buffered (non-acidic) form of vitamin C, was found to be the top lead compound among 106 nutraceuticals against SARS-CoV-2 s M pro [ 36 ], and tizanidine was amongst the 11 approved drugs predicted to show a high binding affinity in VS study with M pro [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phensuximide was found in molecular docking simulations of FDA-approved small compounds associated with protection against COVID-19, M pro [ 35 ]. In VS-based study, magnesium ascorbate, a buffered (non-acidic) form of vitamin C, was found to be the top lead compound among 106 nutraceuticals against SARS-CoV-2 s M pro [ 36 ], and tizanidine was amongst the 11 approved drugs predicted to show a high binding affinity in VS study with M pro [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory interaction between folic acid and the proteolytic protein furin, which was documented to promote activation of the coronavirus, was recently demonstrated [ 33 , 34 ]. Additionally, folic acid and its derivatives were found to have a direct anti-SARS-CoV−2 effect [ 35 , 36 ]. Singh et al proposed the incorporation of folic acid in the treatment regimen of COVID-19 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sapropterin (14.33% inhibition), a phenylalanine-4-hydroxylase stimulant and tetrahydrofolic acid (28.84% inhibition) were also confirmed in vitro to be SARS-CoV-2 inhibitors. Folic acid and its derivatives (tetrahydrofolic acid and 5-methyl tetrahydrofolic acid) have been reported to have good binding affinity to viral proteins in various VS studies (Kumar & Jena, 2020 ). The second pharmacophore search based on the U5P ligand resulted in uridine-5-triphosphate, baicalin, cyclic-AMP, INS316, adenosine phosphate and diadenosine tetraphosphate.…”
Section: Discussionmentioning
confidence: 99%